2014
DOI: 10.1111/echo.12518
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and Lung Ultrasound Characteristics in Ambulatory Patients with Dyspnea or Prior Heart Failure

Abstract: The article by Platz et al. 1 investigates the association of sonographic B-lines, a stated marker of extra-vascular lung water, with cardiac structure and function. The study was performed in a relatively stable outpatient population undergoing transthoracic echocardiography and lung ultrasound imaging (LUS). The count of B-lines, which are "artifacts," is the diagnostic target, which, in our experience, appears inappropriate. 2 B-lines are visible and approximately measured in conditions different from pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Also the observation of the increase of the B-lines with ageing, in subjects without specific heart or chest disease[ 45 , 46 ], is a further argument against any great expectation from this criterion. The use of a criterion with so relevant limitations is not neutral, since it averts from the use of more suitable criteria, such as echocardiography or radiology, or TUS itself, more adequately performed[ 47 - 52 ]. Despite it was claimed that TUS is a basic application in intensive care units and that can become a useful daily tool in these subsets, such application is not generally used and, actually and quite unexpectedly, after so many years, is still under assessment and evaluation.…”
Section: Emergency: Opportunities and Reliabilitymentioning
confidence: 99%
“…Also the observation of the increase of the B-lines with ageing, in subjects without specific heart or chest disease[ 45 , 46 ], is a further argument against any great expectation from this criterion. The use of a criterion with so relevant limitations is not neutral, since it averts from the use of more suitable criteria, such as echocardiography or radiology, or TUS itself, more adequately performed[ 47 - 52 ]. Despite it was claimed that TUS is a basic application in intensive care units and that can become a useful daily tool in these subsets, such application is not generally used and, actually and quite unexpectedly, after so many years, is still under assessment and evaluation.…”
Section: Emergency: Opportunities and Reliabilitymentioning
confidence: 99%
“…Nonetheless, the knowledge of these limitations and the use of the few direct information provided by TUS are a substantial add-on to the clinical strategy of the cardiologist[12], also in emergency[13-15]. …”
Section: Overviewmentioning
confidence: 99%
“…According to their investigation, a specific diagnosis of any pulmonary condition is not reasonably supported on the basis of this criterion, because the measure of B-line number is erratic, as pointed out by others [2], subject to very severe inter- and intraobserver bias [3] and now, thanks to the study just published, strongly depending on the age of the observed patient [1]. Their experience is in agreement with the practice of most echo laboratories.…”
Section: Figmentioning
confidence: 99%